Direct Synthesis of (K0.5Na0.5)NbO3 Powders by Mechanochemical Method - Nguyen Duc Van (Advances in Materials Science and Engineering)
The synthesis and structural properties of lead-free piezoelectric (K0.5Na0.5)NbO3 powders prepared by mechanochemical method using Nb2O5, K2CO3, and Na2CO3 as starting materials were reported. X-ray diffraction, infrared spectroscopy, Raman spectroscopy, and scanning electron microscopy were used to characterize the prepared samples. Results showed that, for the first time, by selecting the milling speed of 600 rpm and the ball-to-powder weight ratio of 35 : 1 as milling parameters, pure (K0.5Na0.5)NbO3 crystalline phase was obtained directly in the as-milled samples after 5 h of milling time. The existence of a carbonato complex between CO32− and Nb5+ ions as an intermediate species of the formation of (K0.5Na0.5)NbO3 was also found.